Integrated process for potassium sulfate and a mixture Of ammonium chloride/potassium sulfate salts production - Mubarak, Yousef (International Journal of Engineering and Technology, 2018)
Relatively pure and coarse crystalline potassium sulfate of about 52 wt % K2O content and almost chlorine free has been obtained by reacting commercial potassium chloride and commercial ammonium sulfate in a stirred tank reactor at moderately low temperature. To increase the yield of potassium sulfate to a reasonable value, an evaporation stage located between the reactor and the crystallizer is used. The main steps of the production process include dissolution, reaction, evaporation, crystallization, centrifuging, drying, and then cooling. It is found that the best operating parameters to produce potassium sulfate of good quality, quantity, and crystal size are 1:1 as KCl/ (NH4)2SO4 mole ratio, 60 ÂºC reaction temperature, 1 hour reaction time, about one third of the total water used in the dissolution step is to be evaporated, 10 ÂºC crystallization temperature, 1 hour crystallization time, and 160 and 60 rpm agitation speeds in the reactor and the crystallizer respectively. Applying these operating conditions, a potassium sulfate yield of about 78 % can be achieved. Also, a fully soluble complex salt as a mixture of ammonium chloride and potassium sulfate is obtained by further treatment of the mother liquor. Further concentration of the mother liquor by further water evaporation of about 40 wt % and then crystallization of the slurry at 25 oC can recover up to about 60 wt % of the remaining solid in the mother liquor as a complex salt. The total yield of potassium sulfate is found to be about 95 wt % and the whole value of the solid product obtained is about 79 wt %.